Fun Learning Arabic Speaking Skills Using Kinemaster Video - Fitri Liza; Miatin Rachmawati; Ayman Shahrour (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2021)
The purpose of this study was to describe how to implement fun learning Arabic speaking using kinemaster video and measure its effectiveness. This research was conducted with a grounded theory qualitative approach. The implementation of this method was carried out on students in grades VII–XI of MTs Muhammadiyah Depok. Methods of data collection included interviews (with the school) and observations (of students' learning conditions).Meanwhile, the data analysis method used three steps, namely data reduction, analysis, and conclusion. The results of this study stated that this fun learning Arabic speaking skills was stimulated by kinemaster video. All materials were included in the video of the drilling process being carried out. After the implementation of the activities, students considered Arabic to be fun, increasing their score to 67% from the initial 33% who thought that learning Arabic was fun. The incoming data said that learning Arabic was very difficult. The meaning was down from the original 65%, while those who think Arabic was boring fell to 31% from the original 69%, and the data also showed a decrease in the very monotonous Arabic learning method, which was originally 63%, now only 37%. These results indicated that the improvement of students' speaking skills should be accompanied by interesting and fun learning methods.